2004
DOI: 10.1177/000331970405500508
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologic Signs for the Inflammatory Role of Chlamydia pneumoniae in the High-Grade Atherosclerotic Coronary Artery Wall

Abstract: The aim of the study was to prove the long-lasting and continuously harmful effect of chronic Chlamydia pneumoniae (CPn) infection on vessel walls in patients with diffuse coronary artery disease (CAD). In surgically obtained endarterectomized atherosclerotic plaques grade VI-VIII (Stary classification) from 10 patients with diffuse coronary artery disease and chronic (7) or past (3) CPn infection, signs of inflammatory response of the vessel wall on infectious agents were studied. In all 10 endarterectomized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Cp infection has been shown to provide continuous and long-lasting inflammatory response in highgrade atherosclerotic coronary artery vessel walls [36]. With current knowledge that Cp can be detected in buffy coat preparations of peripheral whole blood cells and its potential involvement in chronic inflammatory diseases such as atherosclerosis, COPD, bronchitis, and asthma, it was recently suggested that C. pneumoniae be added to the growing list of transfusion-transmitted pathogens [37].…”
Section: Discussionmentioning
confidence: 99%
“…Cp infection has been shown to provide continuous and long-lasting inflammatory response in highgrade atherosclerotic coronary artery vessel walls [36]. With current knowledge that Cp can be detected in buffy coat preparations of peripheral whole blood cells and its potential involvement in chronic inflammatory diseases such as atherosclerosis, COPD, bronchitis, and asthma, it was recently suggested that C. pneumoniae be added to the growing list of transfusion-transmitted pathogens [37].…”
Section: Discussionmentioning
confidence: 99%